AN ANALYSIS OF DEFAULT BETWEEN PT HASPRA KONSULTING WITH PT BAJA BAHAGIA SEJAHTERA: A Case Study on Decision No. 532/Pdt.G/2022/PN/JKT.SEL - Ferdiana, Adela Friska; Nurani, Juli (jfpublisher, 2023)
The default act leads to the right for the injured party to file a lawsuit against the defaulter to provide compensation in order to ensure that there is no one who is legally prejudiced by the default. Unlawful acts are caused by infringement of obligations that come from a contract between the parties involved, such as the default that occurred between PT Haspra Konsulting and PT Baja Bahagia Sejahtera. Therefore, this research aims to determine the default of the cooperation agreement. The research method used is a normative juridical research method, a type of legal research that examines library materials or secondary data of legal material. Meanwhile, the data collection method used is literature research and law study. The research findings indicated that the default that occurred in the cooperation contract related to Decision No. 523/Pdt.G/2022/PN/JKT. SEL, it was found that the judicial decision consisted of granting the Plaintiff’s claim for some part, stating that the Defendant had committed a default by not complying with its obligations in accordance with Cooperation Contract Number P-008/BBS/HAlSPRA/RHS-WFQ/XI/20 on 16 November 2020, punishing the Defendant to compensate the losses suffered by the Plaintiff with the details of payment for Invoice number 045_IV/22/BBS/RHS/HAlSPRA on 19 April for IDR 122,100,000 (one hundred and twenty-two million one hundred thousand rupiah) and to charge the Defendant to pay compensation of IDR 3,755,000 (three million seven hundred fifty five thousand rupiah).